2016
DOI: 10.1016/j.apsb.2016.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of drug release from liquid crystalline monoolein dispersions and solid lipid nanoparticles using a flow cytometric technique

Abstract: Colloidal lipid particles such as solid lipid nanoparticles and liquid crystalline nanoparticles have great opportunities as drug carriers especially for lipophilic drugs intended for intravenous administration. In order to evaluate drug release from these nanoparticles and determine their behavior after administration, emulsion droplets were used as a lipophilic compartment to which the transfer of a model drug was measured. The detection of the model drug transferred from monoolein cubic particles and trimyr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 37 publications
0
13
0
Order By: Relevance
“…Nanoparticles of different chemical natures have been tested for their potential to cross the round window membrane and their capacity to biodegrade [14], including synthetic, amphiphilic, polymeric nanoparticles covalently linked to drugs or interfering RNAs [15,16,17,18]. Lipid nanoparticles are biodegradable and can deliver both hydrophilic and lipophilic drugs depending on their geometry and composition [19,20]. Among the later chemical category, solid lipid nanoparticles (SLNs) are a new generation of submicron-sized lipid particles that present an alternative to the existing lipidic nanocarriers [21].…”
Section: Introductionmentioning
confidence: 99%
“…Nanoparticles of different chemical natures have been tested for their potential to cross the round window membrane and their capacity to biodegrade [14], including synthetic, amphiphilic, polymeric nanoparticles covalently linked to drugs or interfering RNAs [15,16,17,18]. Lipid nanoparticles are biodegradable and can deliver both hydrophilic and lipophilic drugs depending on their geometry and composition [19,20]. Among the later chemical category, solid lipid nanoparticles (SLNs) are a new generation of submicron-sized lipid particles that present an alternative to the existing lipidic nanocarriers [21].…”
Section: Introductionmentioning
confidence: 99%
“…The observed reduction in the interfacial tension of the reconstituted systems suggests that a proportion of the protein content, assumed to be associated with the wax particles prior to freeze-drying, has now been expelled. Several studies in literature concerning drug-loaded solid lipid nanoparticles have reported on the expulsion of the drug molecule to the surface of the crystalline particle as a result of a highly ordered structure (Westesen, Bunjes, & Koch, 1997;zur Mühlen, Schwarz, & Mehnert, 1998;Dawoud & Nasr, 2016). This tendency could also be the case in the investigated lipid particulate systems, which crystallise in the most stable polymorphic forms allowing little space, particularly for a large protein molecule to fit in.…”
Section: Interfacial Behaviourmentioning
confidence: 90%
“…Pure poloxamer 407 exhibited characteristic broad peak at 3425 cm − 1 due to O-H group stretching, 2889 cm − 1 peak indicated C-H stretching vibration, sharp peak at 1596 cm − 1 corresponded to C-C stretching and sharp peak at 1384 cm − 1 indicated nitrate absorption band. Peak at 1113 cm − 1 corresponded to C-O stretching vibration and slight peak at 766 cm − 1 was related to C-N stretch of aromatic and peak at 618 cm − 1 were due to C-H bending [41,42].…”
Section: Drug-excipient Compatibility Studiesmentioning
confidence: 99%